Minimally invasive surgery x conventional surgery on rate recovery rate and aesthetic previsibility: An integrative review (Research, Society and Development, 2021)
Minimally invasive surgery (MIS) is a term that describes noninvasive surgical procedures with or without magnification instruments but there is no scientific evidence yet if there is greater aesthetic predictability and root coverage rate in MIS compared to root surgery conventation. Thus, na integrative literatura review was performed using the following searh strategy: (microsurgery OR surgical AND minimally invasive surgical OR surgery AND gingival recession AND periodontal plastic surgery OR surgical AND root coverage). In Scielo, PubMed, Scopus, Web of Science, Science Direct, BVS and Google Scholar databases using articles published between 2011 – 2020. A total of 546 articles were found and after selection according to the inclusion criteria 05 articles remained for the study all randomized clinical trials. The evaluated information of the articles were their objectives sample size surgical techniques performed the follow – up time and the results and conclusion. Based on the analysis it can be concluded that the MIS does not required the use of magnification instuments. Tunneling performed for root coverage provides better results such as tissue and aesthetic gain over the Coronal Traction Flap especially for Miller classes I and II. The use of connective graft associated with MIS increased the predictability of satisfactory results.